Kazakhstan and India: perspectives in cooperation (Халықаралық қатынастар және халықаралық құқық сериясы, 2016)
Diplomatic relations between Kazakhstan and India were established on February 23, 1992. In May, 1992 the Embassy of Republic of India in Almaty was open, and in November, 1993 the Embassy of the Republic of Kazakhstan in Delhi is opened. The Indian economy - one of most dynamically developing on a planet. In the early nineties in foreign policy strategy of India was a new direction – Central Asia. India attaches great value to development of the relations with Central Asia; initiative so-called “A new Silk way of the Indian foreign policy”, directed on further strengthening of cooperation with the Central Asian region.The important instrument of development and deepening of bilateral cooperation in various spheres is theIntergovernmental Kazakhstan-Indian Joint commission on trade and economic, scientific and technical, industrial and cultural cooperation. Kazakhstan and India will intend to deepen cooperation in the oil and gas sphere. Kazakhstan is open for building of the Indian investments in priority sectors of economy – small and medium business, health care, agriculture, building of objects of Astana.